Therapeutic experience and key techniques of tubeless percutaneous nephrolithotomy - Yuanpeng Zhang; Xinwei Li; Gen Yang; Lei Liu; Xiaoping Zhang; Wencheng Li (Scientific Reports)
Abstract The tubeless percutaneous nephrolithotomy (PCNL) is highly favored by endourological urologists for its advantages in patient experience and length of hospital stay. However, there is currently no guideline or consensus that precisely describes tubeless PCNL. This study explores tubeless PCNL from two aspects: patient selection and technical improvements. Clinical data of 40 cases of conventional PCNL and tubeless PCNL patients operated by the same surgeon between December 2023 and April 2024 were analyzed. The changes in the preoperative and postoperative renal function, hemoglobin and inflammatory markers were evaluated, and the operative time, pain scores, and length of hospital stay were also included. Both groups of patients achieved complete stone clearance (100%). Compared to the conventional PCNL group, the tubeless PCNL group had lower pain scores (P < 0.001) and shorter hospital stays (P = 0.005). There were no statistically significant differences between the two groups in terms of operative time (P = 0.83), renal functional impact (P = 0.699), hemoglobin reduction (P = 0.93), and changes in inflammatory markers (P > 0.05). Tubeless PCNL demonstrated better patient experience and shorter hospital stays. Tubeless PCNL patients were strictly selected according to our criteria and operated based on traditional experience and the improved technical standards in this study. Tubeless PCNL is safe and feasible under these conditions. Retrospectively registered: 0620, August, 2024.